Sistem Monitoring Energi Surya Jarak Jauh - Mahmuddin, Faisal; Rivai, Haryanti; Sammang, Muhammad (Jurnal Penelitian Enjiniring, 2022)
Renewable energy acts as an alternative to non-renewable energy such as fossil fuels. One of the energy that can be renewed is energy from sunlight. This energy is available every day and spread in all regions on earth. Solar energy received in Indonesia is approximately 4.5 kWh/m2/day in the western region and 5.1 kWh/m2/day for the eastern region. This sunlight will later be converted into electrical energy and used for human needs. One of the tools that can be used to capture solar energy is solar panels, the installation of solar panels is mostly still in a fixed or stationary state. This causes the absorption of solar energy is not optimal. Thus it requires the position of solar panels that are always perpendicular to the direction of incoming sunlight, for this reason a device or automatic system is needed that can move solar panels to always be perpendicular to the direction of incoming sunlight. Solar tracking system is a system that can move the solar panel so that the position of the solar panel always follows the direction of incoming sunlight as it has been set in such a way. By using an Arduino microcontroller, where the monitoring process is based on visual basic which is connected to a wireless system in the form of a transmitter & receiver, the solar panel can be moved according to the angle of incidence of sunlight automatically. With the use of solar tracking system on solar panels can increase the average output voltage to 0,895 % and increase the reception of sunlight intensity up to 29,123 % compared to fixed solar panels.